The Prognostic Significance of Circulating Tumor Cells in Patients with Pancreatobiliary Cancer - Ünek, İlkay Tuğba and Öztop, İlhan and Başbınar, Yasemin and Ünek, Tarkan and Leblebici, Asım and Karaca, Caner and Çakıroğlu, Ece and Uysal, Tuğba and Aysal, Anıl and Ellidokuz, Hülya and et al. (Turkish Journal of Gastroenterology, 2023)
Background: Circulating tumor cells (CTCs) are cancer cells which separate from the primary tumor and enter systemic circulation. In this study, it was aimed to examine the relationship between CTCs isolated and identified from the peripheral blood of patients with pancreatobiliary cancer, with the clinicopathological characteristics of the patients and their overall survival. Methods: A total of 21 patients were included the study. Density gradient centrifugation with the OncoQuick® assay was performed for isolation of CTCs from peripheral blood. In order to identify CTCs, enriched samples underwent flow cytometric analysis. Results: The rate of patients with positive surgical margin in the high CTC group (CTC >15) was identified to be statistically significantly high compared to the group with low CTC (CTC ≤15) (83.3% vs. 16.7%; P = .041). Median neutrophil/lymphocyte ratio (NLR) was found to be higher in the high CTC group compared to the low CTC group, which was close to statistical significance (2.37 vs. 1.41; P = .055). Conclusions: Circulating tumor cells were identified to have a significant relationship with surgical margin positivity in our study for the first time, suggesting that the CTCs count in peripheral blood in preoperative patients may be a biomarker predicting positive surgical margin. Due to the very low number of studies assessing the relationship between CTCs and NLR, our study which identified relationship close to statistical significance between CTCs and NLR, significantly contributes to the literature on the topic of the possible role of lymphocytes in CTC clearance. Cite this article as: Ünek İT, Öztop İ, Başbınar Y, et al. The prognostic significance of circulating tumor cells in patients with pancreatobiliary cancer. Turk J Gastroenterol. 2023;34(3):278-286.